Enhancement of speech-in-noise comprehension through vibrotactile stimulation at the syllabic rate - Guilleminot, Pierre; Reichenbach, Tobias (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Speech unfolds over distinct temporal scales, in particular, those related to the rhythm of phonemes, syllables, and words. When a person listens to continuous speech, the syllabic rhythm is tracked by neural activity in the theta frequency range. The tracking plays a functional role in speech processing: Influencing the theta activity through transcranial current stimulation, for instance, can impact speech perception. The theta-band activity in the auditory cortex can also be modulated through the somatosensory system, but the effect on speech processing has remained unclear. Here, we show that vibrotactile feedback presented at the rate of syllables can modulate and, in fact, enhance the comprehension of a speech signal in background noise. The enhancement occurs when vibrotactile pulses occur at the perceptual center of the syllables, whereas a temporal delay between the vibrotactile signals and the speech stream can lead to a lower level of speech comprehension. We further investigate the neural mechanisms underlying the audiotactile integration through electroencephalographic (EEG) recordings. We find that the audiotactile stimulation modulates the neural response to the speech rhythm, as well as the neural response to the vibrotactile pulses. The modulations of these neural activities reflect the behavioral effects on speech comprehension. Moreover, we demonstrate that speech comprehension can be predicted by particular aspects of the neural responses. Our results evidence a role of vibrotactile information for speech processing and may have applications in future auditory prosthesis.
CRIS-Team Scopus Importer:2022-04-15
Keywords: audiotactile integration; EEG; speech-in-noise comprehension